An Analysis of Students’ Ability in Translating Text - desi andriani (Universitas Lancang Kuning, 2020)
Translating text is look like an easy work, but it is a complicated job. A translation text may not have different meaning from the source text to the target language of the text. Translating text from Indonesia to English should not change the sense of language since our culture is different from abroad culture. Translating text from Indonesia to English is more difficult than from English to Indonesia. Since, English has grammar where grammar should not be error. Then, translator also should pay attention to word choice of English. The purposes of carrying this research are to know students’ ability in translating text and common errors made by students in translating text from English to Indonesia at English education students of UPI YPTK Padang in 2019/2020 academic year. This research was descriptive one. The sample of this research was 30 students of English study program of UPI YPTK Padang. The data were collected by using test. The result of the test showed that students had different ability in translating text. In general, students’ ability in translating text was categorized good.